Measurement of Spontaneous Signal Fluctuations in fMRI: Adult Age Differences in Intrinsic Functional Connectivity - Chen, Nan-kuei (2009)
Functional connectivity (FC) reflects the coherence of spontaneous, low-frequency fluctuations in functional magnetic resonance imaging (fMRI) data. We report a behavior-based connectivity analysis (BBCA) method, in which whole-brain data are used to identify behaviorally-relevant, intrinsic FC networks. Nineteen younger adults (20-28 years) and 19 healthy, older adults (63-78 years) were assessed with fMRI and diffusion tensor imaging (DTI). Results indicated that FC involving a distributed network of brain regions, particularly the inferior frontal gyri, exhibited age-related change in the correlation with perceptual-motor speed (choice reaction time; RT). No relation between FC and RT was evident for younger adults, whereas older adults exhibited a significant age-related slowing of perceptual-motor speed, which was mediated by decreasing FC. Older adults' FC values were in turn associated positively with white matter integrity (from DTI) within the genu of the corpus callosum. The developed FC analysis illustrates the value of identifying connectivity by combining structural, functional, and behavioral data.